The limits of polymorphism in Liolaemus rothi: Molecular and phenotypic evidence for a new species of the Liolaemus boulengeri clade (Iguanidae, Liolaemini) from boreal Patagonia of Chile - Pincheira Donoso, Daniel (2007)
Liolaemus hermannunezi is described as a new iguanian lizard species from boreal Patagonia in central-southern Chile. This species occurs in the southeastern areas of Laguna del Laja, in Los Barros and the Río de Los Pinos basin, Antuco Volcano, between 1428 and 1521 m in the Andes of the Bio Bio Region. The new species has previously been identified as L. rothi, related to L. morenoi and L. sagei. Evidence of divergence in morphological, biogeographic, and molecular characters supports significant differences between this Chilean population and L. rothi, L. morenoi and L. sagei. Liolaemus hermannunezi is known from the boreal Patagonia in Chile, while L. rothi is endemic to the Argentinean Patagonia. Like those Liolaemus species, L. hermannunezi is a member of the fitzingerii complex, diagnosed by the presence of a patch of abruptly enlarged scales on the posterior medial surface of the thigh, a more conspicuous character in adult males due to the hypertrophy of the puboischiotibialis muscle (see Etheridge 1995), being characterized by its small body size, peculiar pattern of coloration and latitudinally isolated from L. morenoi, L. rothi and L. sagei, and altitudinally from L. morenoi and L. sagei. Previous observations on the distribution of Liolaemini species suggest that Laguna del Laja could constitute a zone of endemism with an Argentinean range comprised between the northern area of the Neuquen Province and the boreal Patagonia, until 37°50? as southern limit, on which we discuss. Finally, an extensive phylogenetic reconstruction of the Liolaemus genus, based in DNA sequences, is presented.